Description of Students' Knowledge, Attitude, And Behavior Towards Scabies In Al-Firdaus Boarding House, Buntet Islamic Boarding Scabies, Cirebon Regency - Nadella Mutiara Wulandari; Frista Martha Rahayu; Muhammad Suhanda (International Journal of Health and Pharmaceutical (IJHP), 2025)
Scabies is a significant public health issue in densely populated environments like Islamic boarding schools, where high transmission rates are linked to poor hygiene and limited awareness. This study aimed to describe the levels of knowledge, attitudes, and behaviors of students regarding scabies at the Al-Firdaus Dormitory, Buntet Islamic Boarding School, Cirebon Regency. A quantitative descriptive design with a cross-sectional approach was used. The study population consisted of 130 students, from which a sample of 98 was selected using simple random sampling. Data were collected using a validated questionnaire and physical examinations, and were analyzed using univariate analysis. The findings revealed that a majority of students had good knowledge (73.5%), a good attitude (56.1%), and good behavior (53.1%) toward scabies. Despite these positive indicators, 16.3% of the students were found to have scabies, suggesting a gap between awareness and consistent practice. The study concludes that while most students possess a high level of knowledge and a positive attitude, behavioral and environmental factors remain crucial challenges. Targeted interventions focused on practical hygiene training and improved living conditions are essential to effectively reduce scabies prevalence.